2009
DOI: 10.1002/jmv.21611
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diarrhea viruses in hospitalized children in Hong Kong in 2008

Abstract: A total of 209 stool samples were collected from pediatric patients admitted for acute gastroenteritis in a hospital in Hong Kong, during an 8-month period from January to August 2008, and were tested for the presence of rotavirus, norovirus, sapovirus, adenovirus, and astrovirus using a multiplex RT-PCR assay. The most common virus was rotavirus group A (59 of 209, 28%, mainly serotypes G1, G2, G3, and G9), followed by norovirus group II (48 of 209, 23%), adenovirus (7 of 209, 3%, serotypes 2, 3, and 41), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
6
12
1
Order By: Relevance
“…The proportion of positive samples was higher than or equal to previous reports from different countries [9,15]. RV was the most frequently detected infection at 27.94%, which was similar to the level of infection in Hong Kong [16] and India [17]. However, the level of infection was lower than that in other studies, which reported infections up to 54.0% [7,18], and higher than that in France (17.3%) [15].…”
Section: Discussionsupporting
confidence: 69%
“…The proportion of positive samples was higher than or equal to previous reports from different countries [9,15]. RV was the most frequently detected infection at 27.94%, which was similar to the level of infection in Hong Kong [16] and India [17]. However, the level of infection was lower than that in other studies, which reported infections up to 54.0% [7,18], and higher than that in France (17.3%) [15].…”
Section: Discussionsupporting
confidence: 69%
“…Epidemiological studies of adenovirus in infants and children with acute gastroenteritis have shown its importance in both developed and developing countries (6,10,11,17,18,23,31,39,43,49). Next to rotavirus, enteric adenovirus has been shown to be the most common cause of pediatric viral gastroenteritis in Kolkata (31).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the severity of sapovirus gastroenteritis is milder than that for rotavirus and norovirus (Table 5) (185,186,191). Gastroenteritis symptoms are usually self-limiting, and patients usually recover within a couple of days; however, the symptoms, severity, and duration of disease are dependent on the individual, and sapovirus infection sometimes leads to hospitalization (22,152,167,(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)(209). Mortality is rare, but it was reported from outbreaks that occurred in a long-term-care facility for the elderly (104).…”
Section: Symptoms and Severity Of Diseasementioning
confidence: 99%